Training of African nurses in Nyasaland (Malawi) from 1889 to 1927 - J. Smit (AOSIS, 1988)
When the first pioneer missionaries arrived in Nyasaland during I860 there was no educational system in operation according to Western standards. The training of nurses (male and female) therefore evolved as the educational system developed. Before 1900 the training of nurses was done independently by each mission, only providing staff for their local clinics and hospitals. Although the missions worked in different areas of the country, they realised from the start that they should co-operate to achieve results in the medical, educational and technical fields of their work. The Protestant Missions therefore held a series of general missionary conferences where they discussed the different aspects of their work. Six such conferences were held. During the second conference in 1904, an educational code was drawn up and accepted by the missions of the whole Protectorate. During this conference three standards of training was suggested namely that of dressers, hospital attendants and medical assistants. The different syllabuses were discussed. On the suggestion of the Commissioner of the Protectorate, a Medical Board was formed during 1905, to plan for training courses and arrange for examinations. This Board consisted of government and mission representatives. During 1909 the medical courses became more refined. The government did not take part in the training of nurses hut was willing to employ as many nurses as the missions could manage to train. The education system began to develop steadily but then in 1914-1918 war came which caused much disruption. The years of 1919 to 1925 were years of recovery. The education was again stimulated by the visit of the Phelps-Stokes Commission during 1924 which recommended a policy of cooperation in education between Government and Missions. A Department of Education was formed during 1926 and it was decided that vocational schools, which included schools where medical assistants and dispensers were trained, should he under the control of the Department. During 1926 a Medical Council was formed which laid down the standards of courses and examinations of medical assistants. Section 18 of the Medical Practitioners and Dentist's Ordinance of 1926 also made provision for a sub-register to he kept for the registration of medical assistants. This gave well trained Africans standing in their own country and was gladly welcomed by the missions. The African nurses were of sound Christian character and respected by all the peoples in the country. The missionaries felt that the training of medical personnel was one of their best contributions to the medical services and to the population of the country.